Nerves within bone and their application in tissue engineering of bone regeneration - Liu, Songyang; Liu, Shen; Li, Shuming; Liang, Boran; Han, Xiao; Liang, Yonghui; Wei, Xing (Frontiers in Neurology, 2023)
Nerves within bone play an irreplaceable role in promoting bone regeneration. Crosstalk between the nerve system and bone has arisen to the attention of researchers in the field of basic medicine, clinical medicine, and biomaterials science. Successful bone regeneration relies on the appropriate participation of neural system components including nerve fibers, signaling molecules, and neural-related cells. Furthermore, more about the mechanisms through which nerves took part in bone regeneration and how these mechanisms could be integrated into tissue engineering scaffolds were under exploration. In the present review, we aimed to systematically elaborate on the structural and functional interrelationship between the nerve system and bone. In particular, peripheral nerves interact with the bone through innervated axons, multiple neurotrophins, and bone resident cells. Also, we aimed to summarize research that took advantage of the neuro-osteogenic network to design tissue engineering scaffolds for bone repair.